2020
DOI: 10.1002/biot.202000013
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Gut Microbiome for Treatment of Obesity: A Review of Current Understanding and Progress

Abstract: Obesity is a complex, multifactorial disease that is increasing in prevalence despite extensive research and efforts to curb it. Over the last decade, gut microbiome has emerged as an important contributor to the pathogenesis of obesity. Microbiome profile is altered in obese phenotype and the causative role of microbiome in obesity is demonstrated in fecal microbiota transplantation studies. Herein, recent evidences supporting the role of gut microbiome in obesity and the current therapies designed to enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 89 publications
(88 reference statements)
0
18
0
Order By: Relevance
“…We also observed an increase in the abundance of 4 MGs involved in the biosynthesis of peptidoglycans in the obese line: erfK, pbp2A , and mpl (0.63–0.42 SD, P 0 ≥ 0.97), and ftsI with lower evidence (0.12 SD, P 0 = 0.71). Bacterial lipopolysaccharides and peptidoglycans are microbiota-derived endotoxins mainly found in Gram-negative bacteria 30 , 67 contributing to metabolic endotoxemia 25 , 26 and fat-mass development 18 , 22 , 23 , 26 by boosting intestinal permeability 26 , 41 , 68 , 69 and triggering proinflammatory responses when binding CD 14 , TLR 4 27 (lipopolysaccharides), and NOD 1 and NOD 2 12 , 28 30 (peptidoglycans) host receptors. Besides, obese line harbored an increased abundance of 2 MGs involved in the metabolism of lipoproteins: apolipoprotein N-acyltransferase lnt and lipoprotein ygeR (0.41 and −0.38 SD, P 0 ≥ 0.95).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed an increase in the abundance of 4 MGs involved in the biosynthesis of peptidoglycans in the obese line: erfK, pbp2A , and mpl (0.63–0.42 SD, P 0 ≥ 0.97), and ftsI with lower evidence (0.12 SD, P 0 = 0.71). Bacterial lipopolysaccharides and peptidoglycans are microbiota-derived endotoxins mainly found in Gram-negative bacteria 30 , 67 contributing to metabolic endotoxemia 25 , 26 and fat-mass development 18 , 22 , 23 , 26 by boosting intestinal permeability 26 , 41 , 68 , 69 and triggering proinflammatory responses when binding CD 14 , TLR 4 27 (lipopolysaccharides), and NOD 1 and NOD 2 12 , 28 30 (peptidoglycans) host receptors. Besides, obese line harbored an increased abundance of 2 MGs involved in the metabolism of lipoproteins: apolipoprotein N-acyltransferase lnt and lipoprotein ygeR (0.41 and −0.38 SD, P 0 ≥ 0.95).…”
Section: Resultsmentioning
confidence: 99%
“…Bäckhed et al 16 were the first to report a striking difference in body-fat content observed between germ-free mice and conventionally raised mice, with the latter having 40% higher body-fat content 16 . After that, several studies have established that microbial pathways can contribute to obesity by altering apetite 24 , energy extraction from ingesta 17 – 23 , and inflammation and immunity processes via an increased production of microbial-derived metabolites 12 , 18 , 21 – 23 , 25 30 . At the same time, the gut microbiome composition is partially determined by the genes of the host 31 , 32 , as for example, host genes regulating the pH and redox conditions, motility of the intestinal tract, immune response, or the presence of receptors responding to metabolites with microbial origin 33 38 .…”
Section: Introductionmentioning
confidence: 99%
“…The production of these metabolites, the integrity of gut mucosa and consequently the actions that gut bacteria would exert as a whole, would depend on the abundance and proportion of each bacterial taxa inhabiting our intestine. Determinants of gut microbiota composition include dietary intake or antibiotic treatment, among other exogenous and endogenous factors (20,30,135,136). Disruption of the gut bacterial equilibrium results in the deregulation of host metabolic functions and triggers the onset of obesity and obesity-related metabolic diseases (100,112).…”
Section: Gut Microbiota Antibiotic Therapy and Metabolic Diseasesmentioning
confidence: 99%
“…Studies with various methods have shown associations between obesity and the gut microbiota, but not valid and congruent characteristics of the abnormal faecal microbiota (dysbiosis) [2,3,5]. Attempts to restore a normal bacterial composition for the prevention or treatment of obesity have not so far reached established clinical practice [5,6]. Irritable bowel syndrome (IBS), a common comorbidity in subjects with obesity, has also been associated with faecal dysbiosis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%